The Impact of Corporate Culture Promotion on Firm Financial Performance during the War: A Case Study in Sudan - Mousa, Ezzat Kamal Abdalla; Youssef, Osama Abdelmong; Mohamed, Mohamed adel (Journal of Cultural Analysis and Social Change, 2025)
This study to check out to whether culture organization affects firm financial performance in sudan in terms of institution government during the war and innovation and leanrning. We find consistent evidence that corporate culture is positive effected by war from different orientation of employees, also positively related to innovation and learning output and significantly affected by related to firm financial performance. In addition, the negative effect of corporate culture promotion on firms located in less developed provinces. Furthermore, we find that some specific corporate culture, such as innovation culture and integrity with objective the institutions reduce performance.